An Expert System for Fire Prevention in High Rise Buildings - Wayakone, Sengdao (1998)
An expert system (ES) for fire prevention in high rise buildings was developed through a combination of interviews with domain experts and the statistical analysis of the thirteen years secondary data on the types and sources of fire breakouts in buildings from Department of Fire and Rescue, Malaysia. The problems related to fire prevention in high rise buildings, especially in the case of emergency and translation of the experts' knowledge into specific rules were analysed and incorporated into the ES. The stepwise regression analysis was used to test the data. The data and information were stored in databases and could be updated and referred through the ES. This program acts as an adviser for educating people who live in high rise buildings, so as to develop their awareness for better prevention of fire, or in evacuation process during an emergency. In addition, the ES helps fire engineers, architectures and managers in decision making on fire prevention designs based on the Uniform Building By-Law and available documentation.